2002
DOI: 10.2188/jea.12.40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Body Mass Index and Smoking on All-cause Mortality among Middle-aged and Elderly Japanese.

Abstract: To investigate effects of low body mass index (BMI) and smoking on all-cause mortality among middle-aged and elderly Japanese, we conducted a community-based prospective study. A mail survey was conducted in 1987-1990 in four towns, western Japan. A cohort of 7,301 Japanese men and 8,825 Japanese women was followed up from the date of the mail survey to 1995 in three of the towns and 1998 in the fourth town. We investigated the effect of BMI and smoking on all-cause mortality by using Cox's proportional hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…[22][23][24] Our findings support the results of previous studies that have shown smokers who have lower BMI values to be at higher risk of death than those who never smoked. 12,23 We found similar Ushaped associations between BMI and all-cause mortality among participants who never smoked, smokers who had fewer than 10 cumulative pack-years and smokers with 10 or more packyears.…”
Section: Discussionsupporting
confidence: 89%
“…[22][23][24] Our findings support the results of previous studies that have shown smokers who have lower BMI values to be at higher risk of death than those who never smoked. 12,23 We found similar Ushaped associations between BMI and all-cause mortality among participants who never smoked, smokers who had fewer than 10 cumulative pack-years and smokers with 10 or more packyears.…”
Section: Discussionsupporting
confidence: 89%
“…As revealed in several studies, smoking was associated with lower body weight and an increased risk of mortality, and can therefore distort the relationship between BMI and risk of mortality25262728, and adjustment for smoking cannot fully address the issue. Sensitivity analysis by excluding smokers is a more powerful method to address this potential bias.…”
Section: Discussionmentioning
confidence: 99%
“…Although some results from previous studies have showed that obese subjects had much higher risks of death than those of normal weight subjects, 4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] other results have not showed the elevation of the risks. 4,10,18,19,21,[24][25][26][27][28][29] This discrepancy have been attributed to failure to properly take cigarette smoking into account and lack of exclusion of individuals with weight loss-related illness.…”
Section: Effect Modificationmentioning
confidence: 99%
“…Although the adverse health effects of obesity are widely accepted, [1][2][3] the impact of obesity upon mortality is less well established and debates about the effects of leanness still continue. [4][5][6][7] Epidemiologic studies have reported six major patterns regarding the association between body mass index (BMI), weight (kg) divided by the square of height (m), and mortality linearly positive, [8][9][10][11][12][13][14] J-shaped, [11][12][13]15 U-shaped, 4,5,10,12,[16][17][18][19][20][21][22][23][24] inverse J-shaped, 10,19,21,[24][25][26][27][28] linearly inverse, 18,25,29 or no association. 4,27 This discrepancy have been attributed to methodological problems including failure to control for confounding by smoking and failure to exclusion of individuals with weight loss-related illness.…”
mentioning
confidence: 99%